Electroanatomically estimated length of slow pathway in atrioventricular nodal reentrant tachycardia - Irie, Tadanobu (Heart Vessels, 2013)
The length of the slow pathway (SP-L) in atrioventricular (AV) nodal reentrant tachycardia (NRT) has never been measured clinically. We studied the relationship among (a) SP-L, i.e., the distance between the most proximal His bundle (H) recording and the most posterior site of radiofrequency (RF) delivery associated with a junctional rhythm, (b) the length of Koch’s triangle (Koch-L), (c) the conduction time over the slow pathway (SP-T), measured by the AH interval during AVNRT at baseline, and (d) the distance between H and the site of successful ablation (SucABL-L) in 26 women and 20 men (mean age 64.6 ± 11.6 years), using a stepwise approach and an electroanatomic mapping system (EAMS). SP-L (15.0 ± 5.8 mm) was correlated with Koch-L (18.6 ± 5.6 mm; R (2) = 0.1665, P < 0.005), SP-T (415 ± 100 ms; R (2) = 0.3425, P = 0.036), and SucABL-L (11.6 ± 4.7 mm; R (2) = 0.5243, P < 0.0001). The site of successful ablation was located within 10 mm of the posterior end of the SP in 38 patients (82.6 %). EAMS-guided RF ablation, using a stepwise approach, revealed individual variations in SP-L related to the size of Koch’s triangle and AH interval during AVNRT. Since the site of successful ablation was also correlated with SP-L and was usually located near the posterior end of the SP, ablating anteriorly, away from the posterior end, is not a prerequisite for the success of ablation procedures.